The efficacy and safety of fluconazole in preventing invasive fungal infection in very low birth weight infants: a systematic review and meta-analysis - Jinghong Xie; Jiayue Zeng; Shouyan Zheng (BMC, 2023)
Abstract This meta-analysis aimed to assess the efficacy and safety of fluconazole for the prevention of invasive fungal infections (IFI) in very low birth weight infants (VLBWI) and to provide a basis for the clinical use. A detailed search of Pubmed, Embase, Cochrane Library and other databases was performed to carefully screen eligible randomized controlled clinical studies to assess the safety and efficacy of fluconazole in very low birth weight infants in terms of the incidence of invasive fungal infections, fungal colonization rate, and mortality. Our research indicated that the application of fluconazole did not result in intolerable adverse reactions in patients. Fluconazole is effective in preventing invasive fungal infections in very low birth weight infants without serious adverse effects. The dose and frequency of fluconazole in very low birth weight infants still needs to be evaluated in consequent studies.